Answer:
0000000000.00001
Step-by-step explanation:
7ycf6gffty
4(x-2)-3=9
<span>Reorder the terms:
4(-2 + x) + -3 = 9
</span><span>(-2 * 4 + x * 4) + -3 = 9
</span><span>(-8 + 4x) + -3 = 9
</span><span>Reorder the terms:
-8 + -3 + 4x = 9
</span><span>Combine like terms:
-8 + -3 = -11
</span>-11 + 4x = 9
<span>Solving:
-11 + 4x = 9
</span>Add '11' to each side of the equation.
-11 + 11 + 4x = 9 + 11
Combine like terms: -11 + 11 = 0
0 + 4x = 9 + 11
4x = 9 + 11
<span>Combine like terms:
9 + 11 = 20
4x = 20
</span><span>Divide each side by 4.
x = 5</span>
Y = 2x + 4 and y = 3x + 1
Therefore, 2x + 4 = 3x + 1
Answer: You multiply 8 x 3/4=24/4. Then you simplify your answer and it is 6 hours. 24/4 is division 24 divided by 4 equals 6.
Step-by-step explanation: Or, you can change 3/4 to a decimal which is .75. Then you multiply .75 x 8 and the answer is 6.00 which is 6 hours because you do not use the zeros after the decimal point.
Answer:
Step-by-step explanation:
Are you trying to find a variable expression? the product of 86 means multiplication so 86*n or 86n. Other than that I dont understand the question.